The cost-effectiveness of PCSK9 inhibitors - The Australian healthcare perspective. (15th September 2018) - Kumar, Radya; Tonkin, Andrew; Liew, Danny; Zomer, Ella
Abstract: Background: For patients in whom statins are not tolerated or effective as monotherapy, proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) represent a new class of lipid lowering therapies that may reduce low-density lipoprotein cholesterol (LDL-C) levels by up to 50% and lower cardiovascular events. While an important treatment option, the cost-effectiveness of PCSK9i in Australia remains unknown. This study aimed to determine the cost-effectiveness of PCSK9i compared to placebo in the prevention of atherosclerotic cardiovascular disease (CVD). Methods and results: A Markov cohort state-transition model was developed in Microsoft Excel. A hypothetical sample of 1000 individuals based on subjects in the Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects with Elevated Risk (FOURIER) trial populated the model. With each five-year cycle, model subjects could have non-fatal CVD events (myocardial infarction and/or stroke), or die from CVD or other causes. Follow-up was simulated for 25 years. CVD risk reduction, cost and utility data were gathered from published sources. At current acquisition prices (AU8174 per person per year), the incremental cost effectiveness ratio (ICER) was AU308, 558 per quality-adjusted life year (QALY) saved. Acquisition prices would need to be reduced to approximately AU1500 per person per annum for PCSK9i to reach the arbitrary cost-effectiveness threshold of AU50, 000 per QALY saved. Conclusion(s): PCSK9i are an effective alternative for those with existing CVD or at high risk of CVD in whom statin therapy alone is ineffective, but are not cost-effective to the Australian healthcare system based on current prices. Highlights: PCSK9 inhibitors are an efficacious alternative for those with statin intolerance. This is the first cost-effectiveness analysis of PCSK9 inhibitors in Australia. The analysis was from the Australian healthcare perspective. The model comprised a secondary prevention population based on the FOURIER study. At current prices, PCSK9 inhibitors would not be considered cost-effective.